(untitled) (INNOVATIVE ECONOMY, 2020)
Zubkov S.O. CONCEPTUAL MODEL OF ORGANIZATIONAL AND ECONOMIC MECHANISM OF MOBILIZATION OF RESOURCE POTENTIAL OF THE TRADE ENTERPRISE Purpose. The aim of the article is to substantiate the constituent elements of the organizational and economic mechanism of mobilization of the resource potential of the enterprise. Methodology of research. The following methods are used in the article, namely: monographic – to study the works and substantiate own interpretation of the concept of organizational and economic mechanism of mobilization of resource potential of the enterprise; systematization and generalization – selection of components of the organizational and economic mechanism of mobilization of resource potential of the enterprise; analysis and modelling – development of a model of organizational and economic mechanism for mobilizing the resource potential of the enterprise. Findings. The author’s interpretation of the concept “organizational and economic mechanism of mobilization of resource potential of the enterprise” is presented. The model of the organizational and economic mechanism of mobilization of resource potential of the enterprise is developed and the constituent elements of the organizational and economic mechanism of mobilization of resource potential of the enterprise are substantiated. It is proved that the construction of organizational and economic mechanism of mobilization of resource potential of the enterprise should combine a significant set of elements, the quality of formation and application of which depends on the effectiveness of measures to mobilize various elements of resource potential, which, of course, should affect the efficiency of the enterprise, especially in economic and financial crises. Originality. A conceptual model of the organizational and economic mechanism to ensure the mobilization of the resource potential of the trade enterprise, which includes the purpose and objectives, principles, subjects and objects of mobilization; support subsystems, functional, target; methods, ways and tools of resource potential mobilization. Practical value. The obtained results can be used in the activities of trade enterprises during the formation of the system of mobilization of resource potential to increase the efficiency of its use. Key words: model, enterprise, mechanism, organizational and economic mechanism, resource potential.